2012
DOI: 10.1242/dev.077388
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signaling regulates smooth muscle precursor development in the mouse ureter

Abstract: SUMMARYSmooth muscle cells (SMCs) are a key component of many visceral organs, including the ureter, yet the molecular pathways that regulate their development from mesenchymal precursors are insufficiently understood. Here, we identified epithelial Wnt7b and Wnt9b as possible ligands of Fzd1-mediated -catenin (Ctnnb1)-dependent (canonical) Wnt signaling in the adjacent undifferentiated ureteric mesenchyme. Mice with a conditional deletion of Ctnnb1 in the ureteric mesenchyme exhibited hydroureter and hydrone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…Another important observation from these studies is that conditional genetic depletion of BMPR2, stabilization of β-catenin in ABCG2 + MPCs, as well as bleomycin injury in vivo resulted in expansion of the progenitor pool, while terminal contractile function was not achieved. Previous studies have also reported the expansion of undifferentiated progenitor pools in other systems as a result of genetic depletion of BMPR, a decrease of BMP signaling, or an increase of β-catenin activation (80)(81)(82)(83)(84)(85)(86)(87)(88). Conditionally decreased BMPR signaling in adult mice drove the expansion of progenitor pools in which terminal differentiation in multiple cell types was inhibited via the activation of β-catenin signaling (80)(81)(82).…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Another important observation from these studies is that conditional genetic depletion of BMPR2, stabilization of β-catenin in ABCG2 + MPCs, as well as bleomycin injury in vivo resulted in expansion of the progenitor pool, while terminal contractile function was not achieved. Previous studies have also reported the expansion of undifferentiated progenitor pools in other systems as a result of genetic depletion of BMPR, a decrease of BMP signaling, or an increase of β-catenin activation (80)(81)(82)(83)(84)(85)(86)(87)(88). Conditionally decreased BMPR signaling in adult mice drove the expansion of progenitor pools in which terminal differentiation in multiple cell types was inhibited via the activation of β-catenin signaling (80)(81)(82).…”
Section: Methodsmentioning
confidence: 91%
“…In contrast, increased noncanonical Wnt signaling in endothelial cells increases their survival and decreases vascular pruning in vivo and in vitro (94). Canonical Wnt/β-catenin signaling is required for SMC development and terminal differentiation, while in the absence of SMC differentiation, adventitial precursors may proliferate (85). These studies illustrated that a differentiation defect in perivascular cells influences the surrounding mesenchyme as well as fibroblast specification, further illustrating the cell-specific and complex nature of Wnt signaling during vascular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocd , a critical transcription factor required for expression of SMC contractile proteins (αSMA, SM22α and SM-MHC) [37], is dramatically down-regulated in the mutant ureters. Ureter SMC developmental defects are highly associated with defective cell proliferation and survival [9], [10], [28]. In Smad4 CKO embryos, we also detected less proliferative ureteral mesenchymal cells with apoptosis at E14.5.…”
Section: Discussionmentioning
confidence: 62%
“…Although a few genes (e.g., Tbx18 , Sox9 , Tszh3 and β-catenin ) have been identified crucial for ureter development [2], [7][9], the interaction network of these genes with other factors in regulating ureteral SMC development remains to be determined. In this study, we found loss of Smad4 in the ureteral mesenchyme led to failure of SMC differentiation, resulting in severe hydroureter and hydronephrosis during mouse embryogenesis.…”
Section: Discussionmentioning
confidence: 99%